2022
DOI: 10.3390/s22010371
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Localization Using BLE RSSI and Accessible Pedestrian Signals for the Visually Impaired at Intersections

Abstract: One of the major challenges for blind and visually impaired (BVI) people is traveling safely to cross intersections on foot. Many countries are now generating audible signals at crossings for visually impaired people to help with this problem. However, these accessible pedestrian signals can result in confusion for visually impaired people as they do not know which signal must be interpreted for traveling multiple crosses in complex road architecture. To solve this problem, we propose an assistive system calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 38 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Plikynas et al presented an approach to enhance electronic traveling aids for people who are blind or severely visually impaired, using indoor orientation [ 20 ]. Relevant studies have shown that blind people rely on Bluetooth technology [ 21 ], wave radar [ 22 ], and so on when navigating in space. The integration of technology has become very important [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plikynas et al presented an approach to enhance electronic traveling aids for people who are blind or severely visually impaired, using indoor orientation [ 20 ]. Relevant studies have shown that blind people rely on Bluetooth technology [ 21 ], wave radar [ 22 ], and so on when navigating in space. The integration of technology has become very important [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The support-vector-regression-based localization scheme estimates target locations directly through field measurements, bypassing the need for distance computations. Shin et al proposed a crossing assistance system based on RSSI measurement and Bluetooth for outdoor and indoor location tracking [ 37 ]. Herein, we use the KNN method and support vector machine to overcome the problems of the system to enable accurate outdoor positioning.…”
Section: Related Workmentioning
confidence: 99%
“…Martínez-Cruz et al proposed a system where BLE beacons were placed on public transportation buses and their stops to provide real-time guidance to visually impaired users through their smartphones ( 27 ). Another study evaluated the use of BLE beacons to assess impaired pedestrians through a signalized intersection ( 28 ). Hasan and Hasan presented an application of positioning pedestrians in an urban environment through using BLE beacons and the pedestrians’ smartphones ( 29 ).…”
Section: Related Literaturementioning
confidence: 99%